Does neighbourhood composition modify the association between acculturation and unhealthy dietary behaviours?. Issue 8 (3rd March 2015) - Zhang, Donglan; Meijgaard, Jeroen van; Shi, Lu; Cole, Brian; Fielding, Jonathan
Abstract : Objective: Studies have shown that immigrants' acculturation is associated with numerous unhealthy behaviours. Yet, the role of environmental factors in modifying the effect of acculturation on health behaviours has received little attention. This study aims to create a more nuanced understanding of the health effects of acculturation by examining how neighbourhood immigrant composition modifies the association between individuals' eating patterns and acculturation. Methods: Cross-sectional Data from Los Angeles County Health Survey 2007 adult sample were linked to data on retail food establishments and US Census 2000 neighbourhood characteristics. Acculturation was measured by language spoken at home and years stayed in the US. Eating fast food more than once per week and eating zero serving of fruit or vegetables during the previous day were used as proxy indicators for unhealthy dietary behaviour. Multilevel logistic regression models were performed in the full sample and in the sample with only Latino adults. Results: Immigrants' lack of acculturation and living in a neighbourhood with a high percentage immigrants were associated with healthier dietary behaviour. We also identified that lack of acculturation conveyed a significantly stronger protective effect on regular fast-food consumption for immigrants living in neighbourhoods with higher percentage immigrants (OR: 0.34, 95% CI: 0.12 to 0.93). Conclusions: Among immigrants in Los Angeles County, living in a neighbourhood with a high density of other immigrants attenuates the negative effects of acculturation on healthy eating behaviours. Healthy eating promotion efforts should build on this protective effect in outreach to acculturating immigrant communities.